Efeitos da hidroterapia sobre o sistema cardiorrespiratório e manifestações clínicas em mulheres com síndrome fibromiálgica - Andrade, Carolina Pieroni (Universidade Federal de São Carlos, 2018)
Fibromyalgia syndrome (FMS) has multifactorial etiology characterized by various clinical manifestations and low ability to perform physical activities which contributes to low aerobic functional capacity, and consequently worsens pain sensitivity and quality of life. In addition, studies have shown that autonomic dysfunction plays an important role in FMS. Thus, the present thesis consisted of three studies in order to elucidate unknown aspects regarding the aforementioned dysfunctions. The Study I, entitled Reliability of heart period and systolic arterial pressure variabilities in women with fibromyalgia syndrome", aimed to define absolute and relative reliability of spectral indices of cardiovascular autonomic control in the supine position in women with FMS. The results presented good relative reliability, indicating that the indices can be useful as parameters to quantify if a variation was consistent and accurate in the retest besides adding crucial information for clinical research and clinical evaluation of FMS patients. The Study II, entitled "Cardiovascular autonomic control and baroreflex sensitivity after aquatic physical training in women with fibromyalgia: a randomized controlled clinical trial", aimed to evaluate the effect of aquatic physical training (APT) on cardiovascular autonomic control and baroreflex sensitivity (BRS) in women with FMS. After the APT, in supine position, training group (TG) showed a cardiovascular autonomic profile characterized by higher values of HFRR (nu) (p=0.01) and lower values of LFRR/HFRR (p=0.03) and LFSAP (p=0.04) compared to control group (CG). In addition, the indexes of BRS resulted increased in TG compared to CG both in supine (p=0.05) and during standing (p=0.03). The Study III, entitled " Oxygen uptake and body composition after aquatic physical training in women with fibromyalgia: a randomized controlled trial", aimed to investigate whether APT can help improve body composition and increase the aerobic functional capacity in women with FMS, and whether oxygen uptake (VO2) related to lower body mass (LBM) can better quantify the functional capacity of this population. APT with standardized intensities did not cause significant changes in body composition, but was effective in promoting increased VO2 at peak CPET in women with FMS. However, VO2 related to LBM more accurately reflected changes in aerobic functional capacity at ventilatory anaerobic threshold (VAT) level after to APT. The Study IV, entitled “Effects of aquatic training and detraining on women with fibromyalgia: controlled randomized clinical trial” aimed to evaluate variables VO2 relative to LBM and clinical symptomatology in women with FMS submitted to APT and after 16 weeks of detraining period, and to evaluate the association between the magnitude of VO2 improvement relative to LBM and clinical symptomatology. After APT, TG presented an increase in VO2 relative to LBM (p <0.05), in addition to an increase in pressure pain threshold (PPT) and visual analogue scale (VAS) well-being and lower VAS pain and Fibromyalgia Impact Questionnaire score (FIQ) (p <0.05). However, these improvements were not maintained after the 16-week detraining period (p> 0.05). In addition, no significant correlations were observed between improvement of clinical manifestations and increased VO2 relative to LBM after APT (p> 0.05).
Keywords: Síndrome fibromiálgica; Controle autonômico cardiovascular; Sensibilidade barorreflexa; Treinamento físico aquático; Aptidão cardiovascular; Fibromyalgia syndrome; Cardiovascular autonomic control; Baroreflex sensitivity; Aquatic physical training; Cardiorespiratory fitness; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL